Grace and Christianity's Requirement: Moral Striving in Kierkegaard's Judge for Yourself! - Morgan, Jeffrey (Heythrop journal, 2014)
In his later work Judge for Yourself, Kierkegaard presents a view of the Christian life that appears to counter several recent interpretations which situate Kierkegaard within a classical Protestant account of justification and sanctification. I introduce briefly these interpretations and then turn to a reading of Judge for Yourself, showing that Kierkegaard offers an account of grace and moral striving which resists these interpretations. He resists them, yet he presents a Christianity that both rejects works-righteousness and graciously embraces those who confess their failure to do what Christianity requires.